Prediction of the residual stresses and expansion of plastic zones in simply supported thermoplastic composite laminated plates subjected to transverse loads - Arslan, N (Sage Publications Ltd, 2003)
In the present study, the residual stresses and expansion of the plastic zones in simply supported thermoplastic composite laminated plates under uniform transverse loads are given by using FEM. Elastic-plastic stress analysis is carried out for small deformations. Low density homogeneous polyethylene (thermoplastic) and woven stainless steel are used as matrix and fiber materials, respectively. The effect of the reinforcement angle varying from [0degrees/15degrees](2) to [0degrees/90degrees](2) for [0degrees/thetadegrees](2) and from [15degrees/-15degrees](2) to [45degrees/-45degrees](2) for [thetadegrees/-thetadegrees](2) on the residual stresses and the spread of plastic zones are presented. In this analysis, the first-order shear deformation theory is used. The transverse loads are gradually increased from the yield point of the plate by 0.0001 MPa at each load step. Load steps are chosen as 100, 200, 300, 400 and 500. The laminated plates of constant thickness are formed by stacking four layers bonded symmetrically or antisymmetrically.
Keywords: residual stress; plastic zone; thermoplastic laminated composite; elasto-plastic stress analysis; finite element method